Trombone basic skills of students with the new practical hybrid teaching method - Zhang Yi; Pramote Danpradit; Ampaipan Kaosawang (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This is an academic paper intended to suggest ways to resolve the basic skills of trombone students with the new practical hybrid teaching method (NPH) at Shanxi Arts Vocational College. The trombone instruction focuses on developing basic skills such as adjusting the shape of the mouth and wind, determining the pitch of the pitch, etc. During the COVID-19 outbreak, teachers and students were very far apart. Teaching through various online formats was used to help solve the problem of teaching such skills. The researchers reviewed the skills teaching document and proposed teaching methods to modify or improve the key skills of trombone teaching as follows: practical teaching method, demonstration music teaching method, digital music teaching method, reflective music teaching method, and life skills for psychosocial competence. Therefore, the 7 principles that teachers must adapt to suit the context of teaching in their own traditional schools allow teachers to emphasize some issues of appropriateness and spend time teaching.